Strength and Fatigue of Natural and Artificial Materials - Berlin , Al. Al. (Current Innovations in Chemical and Materials Sciences Vol. 3, 2023)
The interpretation of the strength of the composite materials under different external loads as well as the problems of the accumulation of defects in case of large deformations of the material in the solid and liquid states, which ultimately lead to the destruction of the material, are considered. It is proposed that the presence of liquid sap in the tree determines its high fatigue strength.